2011
DOI: 10.2174/1874829501104010112
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Non-Point Source Pollution Around Lake Victoria Using SWAT Model: A Case of Simiyu Catchment Tanzania

Abstract: Pollutant loading in Lake Victoria is resulting from a wide range of anthropogenic activities. This study focused on Non-Point Sources (NPS) of pollution and it was carried out to identify and characterize land-use activities and to quantify the sediment and nutrient loads (nitrogen and phosphorus). The study was conducted in Simiyu catchment of Lake Victoria using land-use data of 1975 and 2006 and comparing the relative impact of land-use change on sediment and nutrient load (P and N) into the lake. Possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 7 publications
(9 reference statements)
2
13
0
Order By: Relevance
“…However the validation iteration captured the low and high flow seasons reasonably well and insynchrony with rainfall pattern (Figures 2a and b). The simulations compared favorably with similar studies on Lake Victoria such as Kimwaga et al (2011) and Opere and Okello (2011) (Figures 3a, b and c). These high water yielding areas not only receive higher precipitation but also have higher slope and the two characteristics mainly explain the water yield.…”
Section: Stream Flowsupporting
confidence: 68%
See 2 more Smart Citations
“…However the validation iteration captured the low and high flow seasons reasonably well and insynchrony with rainfall pattern (Figures 2a and b). The simulations compared favorably with similar studies on Lake Victoria such as Kimwaga et al (2011) and Opere and Okello (2011) (Figures 3a, b and c). These high water yielding areas not only receive higher precipitation but also have higher slope and the two characteristics mainly explain the water yield.…”
Section: Stream Flowsupporting
confidence: 68%
“…The study assessed the impact on change in land cover driven by adoption of modern technology for smallholder dairy industry (Cheruiyot and Muhandiki, 2014b). Kimwaga et al (2011) modeled non-point source pollution in Simiyu watershed in Tanzania using the SWAT model. The study used the model to quantify sediment and nutrient from two land cover scenarios.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between poor land-use practices and NPS pollution was recently established [9][10][11]. Identifying and quantifying NPS hotspots and establishing a relationship between land-use change and water quality deterioration will contribute to the development of strategies for catchment management to control impacts related to the same.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified point source pollution as one of the largest problems causing water quality deterioration in Lake Victoria [9][10][11]. Though enormous attention had been invested in tackling the pollution problem based on point source pollution, recent studies have reported on quantification of Non Point Source (NPS) of pollution into Lake Victoria [9][10][11]. Studying the NPS hot spots and their contribution to lake pollution and relating this to land-use change in the catchment is an important move to set measures for the best management of the catchment land-uses and reduction in deterioration of the lake water quality.…”
Section: Introductionmentioning
confidence: 99%